Literatur Review: Evaluasi Kebijakan Aksi Konvergensi dalam Percepatan Penurunan Stunting di Indonesia - Benita Novia Palastri; Weni Rosdiana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
A literature review on the implementation and evaluation of Convergence Action to Reduce Stunting in Indonesia was conducted as a comprehensive study to understand national patterns, challenges, and factors determining the success of the program. This study aims to examine the effectiveness of cross-sectoral interventions, identify structural barriers, and formulate strategic recommendations for strengthening stunting reduction governance. The method used was a Systematic Literature Review (SLR) with the PRISMA 2020 model, utilizing Crossref and Google Scholar sources through the Publish or Perish application. Of the articles found, only nine studies met the inclusion criteria and were analyzed using a thematic approach based on the CIPP framework. The SLR results showed that in terms of context, government regulations and commitment were strong, but there were geographical disparities, poor sanitation, and low nutrition literacy that affected program outcomes. In terms of inputs, limitations in nutrition human resources, facilities, funding, and the quality of e-PPGBM data were the main obstacles. In terms of process, the implementation of the 8 Convergence Actions has been carried out but remains partial, with suboptimal integration between OPDs and monitoring that has not yet produced adequate feedback. In terms of output, service coverage has increased, but the decline in stunting rates has been inconsistent across regions. The research results emphasize the importance of strengthening human resource capacity, data integration, cross-sectoral coordination, and adapting programs based on local contexts to ensure the accelerated and sustainable reduction of stunting.